POTENTIAL FOR PLASTIC DEGRADATION BY THERMOPHILIC BACTERIA ISOLATED FROM GEOTHERMAL SOURCES OF ZHARKENT (Experimental biology, 2026)
Plastic pollution has become a critical worldwide environmental problem because of the exceptional stability and high resistance of synthetic polymers to natural degradation processes. Plastic waste containing polyethylene terephthalate (PET) is a major contributor to this problem, as PET is one of the most commonly used plastics, and its improper disposal results in its accumulation in nature. The use of thermophilic microorganisms for biotic degradation is one of the environmentally friendly methods that are expected to replace traditional disposal methods. This work aimed at checking the ability of thermophilic bacteria purified from the geothermal springs of the Zharkent region (Kazakhstan) to degrade PET. Water,​‍​‌‍​‍‌ sediment, and soil samples collected from areas where the temperature was between 42 and 103 °C were incubated in mineral salt medium with PET as the only carbon source. We obtained sixteen thermophilic bacterial strains and examined their potential of plastic degradation.After testing the degradation of PET film discs, we found that only four out of those thermophilic strains (W-DP-01, W-DP-03, W-DP-06, SED-02) caused a significant reduction in the polymer weight, i.e., 13.9-16.0 mg, after 28 days of incubation at 65 °C.The Bacillus genus was recognized as the source of the isolates with the outstanding degrading capability of the polymer based on their biochemical and morphological ​‍​‌‍​‍‌characteristics.
Keywords: thermophilic bacteria, polyethylene terephthalate, PET degradation, geothermal sources, Bacillus, biodegradation